2017
DOI: 10.1177/1753944717714921
|View full text |Cite
|
Sign up to set email alerts
|

Nonvitamin K antagonist oral anticoagulant use in patients with renal impairment

Abstract: The nonvitamin K antagonist oral anticoagulants (NOACs), also referred to as direct oral anticoagulants (DOACs), dabigatran, apixaban, edoxaban, and rivaroxaban, have emerged as effective alternatives to vitamin K antagonists (VKAs) across several indications, including the prevention of stroke and systemic embolism (SSE) in patients with atrial fibrillation (AF) and the treatment of venous thromboembolism (VTE). Their use in patients with renal impairment is of particular importance, given the prevalence of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 39 publications
1
44
0
1
Order By: Relevance
“…SPRINT AF also assessed the prevalence of Canadian patients eligible for the reduced dose of apixaban or rivaroxaban. Accordingly, and in agreement with the mentioned studies, more patients were being prescribed with a reduced dose of the factor Xa inhibitors than those who met the reduction criteria . Choosing lower doses reflects a greater concern by the physician to avoid bleeding complications rather than thromboembolic events …”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…SPRINT AF also assessed the prevalence of Canadian patients eligible for the reduced dose of apixaban or rivaroxaban. Accordingly, and in agreement with the mentioned studies, more patients were being prescribed with a reduced dose of the factor Xa inhibitors than those who met the reduction criteria . Choosing lower doses reflects a greater concern by the physician to avoid bleeding complications rather than thromboembolic events …”
Section: Resultssupporting
confidence: 62%
“…Accordingly, and in agreement with the mentioned studies, more patients were being prescribed with a reduced dose of the factor Xa inhibitors than those who met the reduction criteria. 19 Choosing lower doses reflects a greater concern by the physician to avoid bleeding complications rather than thromboembolic events. 44 Real-world studies demonstrated that low doses of dabigatran and edoxaban are preferentially prescribed and their inappropriate low dosing (ILD) is greater than appropriate low dosing.…”
Section: Suboptimal Doacs Use In Clinical Practicementioning
confidence: 99%
See 3 more Smart Citations